Micronodular thymoma with lymphoid stroma: Two cases, one in a multilocular thymic cyst, and literature review. Issue 6 (20th September 2017) - Qu, Linlin; Xiong, Yan; Yao, Qian; Zhang, Bo; Li, Ting
Abstract : Micronodular thymoma with lymphoid stroma (MTWLS) is a rare type of thymoma that shows a similar pattern but varied morphology and immunophenotype of tumor cells. Because of the extremely limited number of cases reported, the pathology and biology of MTWLS are equivocal. Herein, we report two cases located in the anterior mediastinum: Case 1: a 58‐year‐old woman with a cystic mass measuring 5 × 3.0 × 2.5 cm in Mosaoka stage I; and Case 2: a 50‐year‐old man with a solid mass measuring 2.5 × 2.5 × 2.0 cm in stage IIb. Both patients were treated by thymectomy and are alive without recurrence or metastasis 15 and 17 months after surgery, respectively. Regardless of the spectrum of pathology and stage of MTWLS, this unique type of thymoma has a homogeneously favorable prognosis.